Bengal Tigers Are Awesome! - Peterson, Megan Cooley; Gai, Jackie, Wildlife Vet. (London : Raintree, 2016)
"Introduces readers to Bengal tigers, including physical characteristics, behavior, habitat, diet, and life cycle".
A sneaky cat. A Bengal tiger's body. Life in the forest. Growing up Bengal tiger. Saving Bengal tigers.
"Book Band Level: Purple"--Back cover.
Includes bibliographical references and index.
Ages 4-8.
K to grade 3.
Keywords: Bengal tiger -- Juvenile literature; Bengal tiger -- Conservation -- Juvenile literature; Rare mammals -- Juvenile literature